Virtual skin outfit in PUBG mobile games: value and enjoyment with virtual appearance / Noraziah Mohd Razali … [et al.] - Mohd Razali, Noraziah; Harun, Azahar; Abdul Rahim, Ruslan; Michael, Valerie; Muhammad Azmi, Safrina (Faculty of Art and Design, 2024)
Playing games is indisputably one of the most prevalent human activities. Without a doubt, the expansion of mobile gaming is undeniable. Player Unknown's Battle Royale is an exceptionally notable mobile game since 2018. Player Unknown's Battlegrounds (PUBG) has gained worldwide success, attributed to the charming gameplay, tactical component, and "Royale Pass" system, which provides in-game items such as virtual skins. A virtual skin is an in-game item that players may purchase and obtain in-game. These skins have different values according to their rarity. Gamers eagerly anticipate the release of their "Royale Pass" to discover the latest skin variations that cater to their preferences. Previous studies have raised concerns about these gambling-like properties due to the unpredictable and rare opportunities to obtain virtual skins, leading to ambiguity about players' perceptions of the value and enjoyment of these skins. This research aims to explore players' perceptions of the value and enjoyment of virtual skin outfits in the game. A survey was conducted via a questionnaire generated using Google Forms. The research employed convenience sampling as it was based on the accessibility and willingness of the respondents to participate. A total of 30 respondents responded to the question, and a descriptive analysis was performed using the Statistical Package for the Social Sciences (SPSS) to determine the frequencies of the variables indicated. The study's findings indicate that players attribute value to virtual skins due to their design and style of the skin. Thus, they derive enjoyment from using the skins during gameplay. Moreover, the player's enjoyment in the game is influenced by their imagination and emotions, as they find various designs and styles aesthetically pleasing. Each player has their own unique perspective on beauty, and they have the freedom to select any virtual skin that brings them satisfaction in the game.